Young students' aesthetic experiences and meaning-making processes in an outdoor environmental school practice. Issue 2 (3rd April 2017) - Manni, Annika; Ottander, Christina; Sporre, Karin
ABSTRACT: This study uses John Dewey's theoretical concept of 'aesthetic experience' in empirically exploring expressions of cognition and emotion in students' meaning-making processes. A case study was conducted in one class of Grade 6 students during a single school semester. This article reports results from five outdoor days. The empirical material consists of observations, field notes, logbook entries, interviews and students' written reflections. The students' meaning-making processes were analyzed through the Deweyan theory of an initial phase involving anticipation, an activity phase with courses of actions and a concluding phase with reflections that serve as fulfillments. Expressions of aesthetic experience were identified in four important components of the students' meaning-making processes: prior personal experiences; responses to environments and artifacts; social interaction; and situations allowing for responsibility, trust and independence. A more in-depth process-oriented analysis revealed that aesthetic experiences are vital in continuous meaning-making processes.